2015
DOI: 10.3389/fpls.2015.00950
|View full text |Cite
|
Sign up to set email alerts
|

Versatile roles of brassinosteroid in plants in the context of its homoeostasis, signaling and crosstalks

Abstract: Brassinosteroids (BRs) are a class of steroidal plant hormones that play diverse roles in plant growth and developmental processes. Recently, the easy availability of biological resources, and development of new molecular tools and approaches have provided the required impetus for deeper understanding of the processes involved in BRs biosynthesis, transport, signaling and degradation pathways. From recent studies it is also evident that BRs interact with other phytohormones such as auxin, cytokinin, ethylene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
98
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(99 citation statements)
references
References 171 publications
(273 reference statements)
0
98
0
1
Order By: Relevance
“…It has been well known that protein phosphorylation are involved in many different plant hormones such as phosphorylation regulates the polarity of PIN in auxin [3337], gibberellins [33, 38, 39], cytokinin [40], ABA [41] and in BR signaling [4244]. Many studies have demonstrated that MPKKK cascade promotes ACS6 and EIN3 phosphorylation [45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…It has been well known that protein phosphorylation are involved in many different plant hormones such as phosphorylation regulates the polarity of PIN in auxin [3337], gibberellins [33, 38, 39], cytokinin [40], ABA [41] and in BR signaling [4244]. Many studies have demonstrated that MPKKK cascade promotes ACS6 and EIN3 phosphorylation [45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…BZR1 transcription factor plays a key role in the downstream BR signaling pathway, by activating thousands of genes and repressing similar number of genes including BR biosynthetic genes via a feedback loop (Zhu et al 2013). Considering that BRs are unable to be transported long distance, it has been proposed that BZR1 transcription factors may also serve as major connecting points among other signaling pathways (Saini et al 2015). To understand how BRs regulate plant growth and development, as well as, they act in responding to stress conditions, a wide characterization of the transcriptional networks through which BRs regulate gene expression is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…They regulate multiple physiological functions including seed germination, cell elongation and division, senescence, vascular-differentiation, reproduction, root development, photomorphogenesis and respond to various biotic and abiotic stresses (Saini et al 2015;Singh and SavaldiGoldstein 2015). Molecular studies evidenced cross-talk between BRs and other phytohormones and hypothesised the existence of synergistic effects between exogenous BR treatments and endogenous levels of other hormones (Gruszka 2013;Zhu et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…PIFs belong to the basic helix-loop-helix (bHLH) family of TFs and are best known as negative regulators of chlorophyll biosynthesis and photomorphogenesis (Stephenson et al, 2009;Leivar and Quail, 2011;Zhang et al, 2013;Pfeiffer et al, 2014). Brassinosteroids are important regulators of many aspects of plant growth and development, including cell elongation, responses to biotic and abiotic stresses and photomorphogenesis (Saini et al, 2015;Singh and Savaldi-Goldstein, 2015). We decided to explore this PIF/BR regulatory sub-network in more detail since both PIFs and BRs have been implicated in the regulation of chloroplast biogenesis (Stephenson et al, 2009;Leivar and Quail, 2011;Yu et al, 2011;Zhang et al, 2013;Pfeiffer et al, 2014), and may therefore directly affect the physiology and development of mesophyll cells.…”
Section: Gene Ontology Analysis Of the Genes Associated With Cell Typmentioning
confidence: 99%